Analisis Nilai Wajar Saham BJBR dengan Price To Book Value, Dividend Discount Models dan Free Cash Flow To Equity - Mutia, Ajeng Fitriani; Sibarani, Mentiana (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the BJBR stock fundamentally for the period 2020-2024. It uses absolute methods, namely Price To Book Value (PBV), Dividend Discount Models (DDM), and Free Cash Flow To Equity (FCFE), to determine whether the stock is undervalued, overvalued, or fairly valued, and this will also provide investment decision recommendations for investors. This type of research is qualitative with a descriptive approach. The main object of this research is PT. Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk (BJBR Stock) for the period 2018-2022. The sampling technique used in this research is purposive sampling. This company was selected as the object of research considering that it is the largest regional development bank in Indonesia with a substantial total asset. The results of the research using the Price To Book Value (PBV) method indicate that the stock is undervalued. In using the Dividend Discount Model (DDM), the stock is in an undervalued condition. Furthermore, using the Free Cash Flow To Equity (FCFE) method shows that the stock is in an undervalued condition. Factors that also influence the market price of the stock include investors' expectations and perceptions of the bank's performance in the future, so with a perception of declining financial performance, demand decreases and stock prices also decline